2019
DOI: 10.1063/1.5099500
|View full text |Cite
|
Sign up to set email alerts
|

Pore-scale study of counter-current imbibition in strongly water-wet fractured porous media using lattice Boltzmann method

Qingqing Gu,
Lianhua Zhu,
Yonghao Zhang
et al.

Abstract: Oil recovery from naturally fractured reservoirs with low permeability rock remains a challenge. To provide a better understanding of spontaneous imbibition, a key oil recovery mechanism in the fractured reservoir rocks, a pore-scale computational study of the water imbibition into an artificially generated dual-permeability porous matrix with a fracture attached on top is conducted using a recently improved lattice Boltzmann color-gradient model. Several factors affecting the dynamic counter-current imbibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…In order to be computationally admissible and thus allow for parametric studies, we, motivated by Horgue et al (2013) and Sun et al (2016), develop a quasi-3D color-gradient LBM model that is able to accurately simulate immiscible two-phase flows through a Hele-Shaw cell or micromodel. The quasi-3D model can be regarded as a variant of our previous 2D model (Xu et al, 2017), which has shown promise in simulating multiphase flows through complex porous media (Gu et al, 2019;Xu & Liu, 2018), and it is described as follows.…”
Section: A Quasi-3d Color-gradient Lbm Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to be computationally admissible and thus allow for parametric studies, we, motivated by Horgue et al (2013) and Sun et al (2016), develop a quasi-3D color-gradient LBM model that is able to accurately simulate immiscible two-phase flows through a Hele-Shaw cell or micromodel. The quasi-3D model can be regarded as a variant of our previous 2D model (Xu et al, 2017), which has shown promise in simulating multiphase flows through complex porous media (Gu et al, 2019;Xu & Liu, 2018), and it is described as follows.…”
Section: A Quasi-3d Color-gradient Lbm Modelmentioning
confidence: 99%
“…For the details of the wetting boundary condition, interested readers are referred to Xu et al (2017). Recent simulations showed that this wetting boundary condition is able to precisely control the contact angle for both static and dynamic problems with arbitrarily complex geometries (Akai et al, 2018;Gu et al, 2019;Xu & Liu, 2018), which is essential for accurate simulation of two-phase displacement in porous media.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…The LBM is a mesoscopic method based on the discretization of the Boltzmann kinetic equation. The key to this method is to treat the fluid as composed of particles with only mass but no volume and to simulate fluid flow behaviors in rocks by solving distributions of particles in time and space. ,,, With the advantages of clear physical image results, easy treatment of boundary conditions, and fully parallel algorithms, it is suitable to solve challenges that involve complicated boundary conditions and multiphase interfaces in shale imbibition. , For example, Zheng et al adopted modified LBM to simulate spontaneous imbibition behavior in a complicated 3D porous shale structure with intergranular pores, organic pores, and microfractures included . In comparison to the MD approach, LBM is more suitable for flow simulation in pores covering multi-scales.…”
Section: Imbibition Characterizationmentioning
confidence: 99%
“…However, it cannot handle complex geometries properly. Vast literature exists on the application of the Lattice Boltzmann method (LBM) to model two-phase flow in complex geometries. The direct numerical simulations (DNS) method is a reliable approach to handle complex pore geometries by solving the Navier–Stokes equations using finite difference, finite element, and finite volume methods . The most popular interface-capturing methods include the volume of fluid (VOF), level-set, and phase-field methods .…”
Section: Introductionmentioning
confidence: 99%